Dengue and Acute Acalculous Cholecystitis - Meneguelli Nascimento, Magnus (2024)
Acute acalculous  cholecystitis is an inflammatory condition of the gallbladder without evidence of gallstones, and usually appears about two weeks after a serious clinical condition, such as major surgery, severe trauma, large body burns, end-stage renal disease, leukemia, and infections. This clinical experience report discusses this pathology in the medical training, mainly as a sudden and atypical evolution of Dengue. The experience reports on an elderly patient, who only had diffuse myalgia as a previous symptom, quickly evolving into choluria, vomiting, paleness, and abdominal pain. In light with the literature, conservative treatment was chosen, which resulted in rapid clinical improvement. This experience report contributes to the bibliography of an atypical complication of Dengue, highlighting the effectiveness of conservative treatment in this case and enhances the literature regarding medical training.